Developing a new flexible tool for handover. (2nd February 2021) - Magnezi, Racheli; Gazit, Inbal; Bass, Arie; Tal, Orna
Abstract: Background: Transferring medical information among professionals and between shifts is a crucial process, allowing continuity of care and safety, especially for complex patients in life-threatening situations. This process, handover, requires focusing on specific, essential medical information while filtering out redundant and unnecessary details. Objectives: To create and implement a tool for handover that would be flexible enough to meet the unique needs of specific departments. Methods: We used Plan–Do–Study–Act (PDSA) methodology to prospectively develop, implement, evaluate and reassess a new handover tool in a 900-bed teaching hospital in central Israel. Nurses from 35 departments participated in developing a tool that presents the staff's viewpoint regarding the most critical information needed for handover. Results: A total of 78 nurse managers and 15 doctors (63.7%) completed the questionnaire. Based on exploratory factor analysis, 15 items explained 58.9% of the variance. Four key areas for handover were identified, in addition to basic patient identification: (i) updated clinical status, (ii) medical information, (iii) special clinical treatment and (iv) treatments not yet initiated. Subsequently, a Flexible Handover Structured Tool (FAST) was designed that identifies patients' needs and is flexible for the specific needs of departments. Revisions based on hands-on experience led to high nurse satisfaction with the new tool in most departments. The FAST format was adopted easily during the COVID-19 pandemic. Conclusion: Implementing a new handover tool—FAST—was challenging, but rewarding. Using PDSA methodology enabled continuous monitoring, oversight and adaptive corrections for better implementation of this new handover reporting tool.